Anion containing novel porous Manganese-1,2,4-triazolate frameworks as battery-type electrode materials for supercapattery devices - Raman, Velan; Borzehandani, Mostafa Yousefzadeh; Mohammad Latif, Muhammad Alif; Mohamed Tahir, Mohamed Ibrahim; Abdul Rahman, Mohd Basyaruddin; Sulaiman, Yusran (Elsevier, 2024)
Metal-organic frameworks (MOFs) have sparked much attention as electrode material for supercapattery devices due to their unique characteristics, providing porous structures with high surface areas and desirable pore sizes. Three new Mn-organic frameworks were solvothermally synthesised using three different manganese salts (MnX2·4H2O, where X = Cl, Br and NO3) with 1,2,4-triazole (Htrz) ligands. The newly synthesised UPMOFs (Universiti Putra Metal-organic Frameworks) denoted as UPMOF-4[Mn(Htrz)(DMA)Cl], UPMOF-5[Mn(Htrz)(DMA)Br] and UPMOF-6[Mn(Htrz)(DMA)NO3] showed a promising BET surface area of 1758 m2/g, 1724 m2/g and 895 m2/g. Then, the supercapattery device was fabricated using the battery-graded UPMOFs as positive electrodes sandwiched with activated carbon (AC) as a negative electrode. The designed supercapattery devices delivered good specific capacities and specific energies. After 5000 cycles, the UPMOFs showed promising capacity retention of 90.01 % (UPMOF-4), 85.2 % (UPMOF-5) and 76.4 % (UPMOF-6) indicating good stability. Thus, to compare the electrochemical performances among the UPMOFs, a theoretical calculation using the density functional theory (DFT) was performed. The DFT calculation of these UPMOFs revealed that UPMOF-4 had the lowest HOMO-LUMO energy gap (Egap) of 0.211 eV followed by UPMOF-6 (0.777 eV) and UPMOF-5 (1.198 eV). The UPMOF-4 with good framework stability, low Egap and large BET surface area contribute to its promising electrochemical performance.